Exosomes released by environmental pollutant-stimulated Keratinocytes/PBMCs can trigger psoriatic inflammation in recipient cells via the AhR signaling pathway - Kim, Hye Ran; Lee, So Yeon; You, Ga Eun; Park, Chun Wook; Kim, Hye One; Chung, Bo Young (Frontiers in Molecular Biosciences, 2024)
Exosomes, pivotal in intercellular communication during skin disease pathogenesis, have garnered substantial attention. However, the impact of environmental pollutants, such as benzo[a]pyrene (BaP) and 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD), on exosome release amid inflammatory skin diseases remains unexplored. This study addresses this gap by examining the influence of BaP and TCDD on exosome function, specifically focusing on immune-related pathway alterations in normal recipient keratinocytes and peripheral blood mononuclear cells (PBMCs). HaCaT cells were treated with exosomes from BaP- or TCDD-treated keratinocytes. Proinflammatory cytokines and chemokines, including TNF-α, IL-1β, IL-6, IL-8, CXCL1, and CXCL5, were assessed. The involvement of the p65NF-κB/p38MAPK/ERK signaling pathway in recipient keratinocytes was investigated. Aryl hydrocarbon receptor (AhR) silencing was employed to elucidate its role in mediating the proinflammatory response induced by exosomes from BaP- or TCDD-treated keratinocytes. Treatment with exosomes from BaP- or TCDD-treated keratinocytes induced a significant increase in proinflammatory cytokines and chemokines in HaCaT cells. The upregulation implicated the p65NF-κB/p38MAPK/ERK signaling pathway. AhR silencing attenuated this response, suggesting a role for AhR in mediating this response. In PBMCs from healthy controls, exosomes from BaP-stimulated PBMCs of psoriatic patients led to increased expression of proinflammatory cytokines and modulation of Th1/Th17 cell distribution via AhR activation. These findings unveil a novel dimension in the interplay between environmental xenobiotic agents (BaP and TCDD) and exosomal functions. The study establishes their influence on psoriatic inflammatory responses, shedding light on the underlying mechanisms mediated through the AhR signaling pathway in recipient keratinocytes and PBMCs.